2022
DOI: 10.1016/j.jns.2021.120100
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal seizure outcome following the COVID-19 pandemic in 2020 and 2021: Transient exacerbation or sustainable mitigation

Abstract: Objective To study the longitudinal seizure outcomes of people with epilepsy (PWE) following the acute and chronic phases of the coronavirus disease 2019 (COVID-19) pandemic. Methods Consecutive PWE who were treated at the epilepsy center of Hiroshima University Hospital between 2018 and 2021 were enrolled. We evaluated the incidence of seizure frequency increase or decrease following the pandemic during observational periods in 2020 and 2021. Data between 2018 and 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…19,20 Some studies have reported risk factors for seizure exacerbation during the pandemic, regardless of SARS-CoV-2 infection, including epilepsy severity and ASM polytherapy, sleep disorders, social factors, and mental stress in general. [21][22][23][24] Notably, in a surveybased study performed at our epilepsy center between May and July 2020, a clinical worsening was reported in 27 of 222 PWE (12%) and was associated with limited access to health care, among other factors. 23 Epilepsy care was negatively impacted during the pandemic for several reasons, including restricted access to out-and inpatient clinics and routine electroencephalograms, in addition to difficulties related to ASM prescription and testing of blood levels.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…19,20 Some studies have reported risk factors for seizure exacerbation during the pandemic, regardless of SARS-CoV-2 infection, including epilepsy severity and ASM polytherapy, sleep disorders, social factors, and mental stress in general. [21][22][23][24] Notably, in a surveybased study performed at our epilepsy center between May and July 2020, a clinical worsening was reported in 27 of 222 PWE (12%) and was associated with limited access to health care, among other factors. 23 Epilepsy care was negatively impacted during the pandemic for several reasons, including restricted access to out-and inpatient clinics and routine electroencephalograms, in addition to difficulties related to ASM prescription and testing of blood levels.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in a recently published Korean study, PWE underwent a transient seizure exacerbation in 2020, which was followed by a trend toward seizure amelioration in 2021. 24 Additionally, the propensity of emergency department operators to hospitalize PWE with COVID-19 might have been more pronounced during the first epidemic wave, when the clinical features of COVID-19 and its impact on epilepsy were largely unknown. 17 PDEE were the population at highest risk of hospitalization, likely because among PWE they represent the most vulnerable patients, are more frequently institutionalized, and might not be compliant with the use of personal protective equipment, resulting in a higher risk of infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations